If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3cot = 1 Solving 4 + -3cot = 1 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3cot = 1 + -4 Combine like terms: 4 + -4 = 0 0 + -3cot = 1 + -4 -3cot = 1 + -4 Combine like terms: 1 + -4 = -3 -3cot = -3 Divide each side by '-3ot'. c = o-1t-1 Simplifying c = o-1t-1
| 40=8(x-8) | | X^2-12X-4.5=0 | | P=2x+3 | | -8y=-6-9y | | -3(5+2x)=-2x+13 | | 8-(4x-12)=8x-(3x-2) | | 2-5f=-7f+10 | | 4+2y=10-4y | | 3/5=6n | | -j=j-8 | | -5x(4x-8y^2+4)= | | 10-6n=-6-10n | | 3b-11=3+b | | 7x-14=7(x+4) | | 5+10d=9d | | 6x-(10-2x)=3x+5 | | 9b+3=22 | | 18.9125-(1/4)= | | 9b+3=20 | | 9b+3=19 | | 2x^3-11x^2-10x+75=0 | | 9b+3=18 | | 9b+3=16 | | 4(t-3)+6t=5(2t+5)-12 | | 4x+3(2x-1)-4x=x | | a+4=a | | 4b+3=7 | | 4m^2-5=95 | | 2x+1x=126 | | (7)+11= | | -5+4a^2=59 | | 3+2t-1=6t+10-2t |